Participation of Management Study Program Students in International Scientific Conferences: Perspectives and Experience - Rifiyanti, Hafizah (Universitas Terbuka, 2023)
Participation in international scientific conferences is often considered a valuable opportunity for students pursuing higher education, particularly in fields such as management. However, the extent to which Management Study Program students engage in such conferences and the impact of this participation on their academic and personal growth remain relatively underexplored areas of research. The research aims to provide insights into the participation of Management Study Program students in international scientific conferences, shedding light on their motivations, experiences, and the outcomes of such involvement. The descriptive qualitative method is used to analyze the findings in the form of questionnaires given to 15 students of the management study program, Institut Bisnis dan Informatika Kwik Kian Gie who have attended the International Conference event. The general view of the students was that attending international conferences was considered beneficial for improving English language skills, organization, as well as socialization and understanding of diverse cultures although individual experiences and perspectives varied. Positive view towards participation in international conferences and see it as a valuable opportunity to improve their English language skills and their personal and professional development. It is expected that through this research, there will be more in-depth and extended research to investigate participants'' experiences in participating in international conferences